Poly(Pyridinium Salt)s Based on 2,7-Diamino-9,9-Dioctylfluorene Moieties: Synthesis, Lyotropic Liquid-crystalline and Light-emitting Properties - Bhowmik, Pradip K.; Jo, Tae S.; Koh , Jung J.; Park , Jongwon; Biswas , Bidyut; Principe , Ronald Carlo G.; Han , Haesook; Wacha , Andras F.; Knaapila, Matti (Current Topics on Chemistry and Biochemistry Vol. 2, 2022)
The phenylated poly(pyridinium salt)s are a class of ionic main-chain chain polymers that are usually prepared by the ring-transmutation polymerization reaction of bispyrylium salts and diamines, and metathesis reactions. They are touted as advanced functional materials, since they are used for the preparation of electrochromic devices, fire-retardant materials, biosensors, and even nonlinear optical devices. Here we describe a new series of poly(pyridinium salt)s that exhibit lyotropic liquid-crystalline and light emitting properties. A series of poly(pyridinium salt)s-fluorene main-chain ionic polymers with various organic counterions were synthesized by using ring-transmutation polymerization and metathesis reactions. Their chemical structures were characterized by Fourier Transform Infrared (FTIR), proton (1H), and fluorine 19 (19F) nuclear magnetic resonance (NMR) spectrometers. These polymers showed a number-average molecular weight (Mns) between 96.5 and 107.8 kg/mol and polydispersity index (PDI) in the range of 1.12–1.88. They exhibited fully-grown lyotropic phases in polar protic and aprotic solvents at different critical concentrations. Small-angle X-ray scattering for one polymer example indicates lyotropic structure formation for 60–80% solvent fraction. All polymers exhibited lyotropic liquid-crystalline phases in organic solvents (DMSO, CH3CN, or MeOH) above their critical concentrations, depending on the counterions. Polymer 1 was found to show a square packing motif within the observed LC platelets. The analyses of their optical properties revealed that the light emission spectra were dependent on the chemical structures of the counterions in the film states resulting in blue light, and the majority of them emitted green light in organic solvents except in a few cases they emitted blue light in THF. The size of counterions had an impact on the thermal characteristics of polymers, as measured by differential scanning calorimetry and thermogravimetric analysis. Their UV-Vis absorption spectra in various organic solvents were nearly comparable, showing that the closely spaced \(Π\)- \(Π\)*transitions were present in their conjugated polymer architectures.